2019
DOI: 10.3389/fmicb.2019.02500
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Plant Microorganisms Affect the Endophytic Bacterial Communities of Durum Wheat Roots as Detected by Different Molecular Approaches

Abstract: This study aimed at characterising the endophytic bacterial communities living in durum wheat roots, as affected by wheat cultivar and inoculation of the Arbuscular mycorrhizal fungus Funneliformis mosseae IMA1 and the wheat root endophytic bacterium Lactobacillus plantarum B.MD.R.A2. These microorganisms were inoculated, alone or in combination, in durum wheat (cultivars Odisseo and Saragolla). Non-inoculated plants of each cultivar represented the controls. Forty-three days after sowing, roots were deprived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 68 publications
(86 reference statements)
1
30
0
Order By: Relevance
“…Lactobacillus sp. is one of many commensal epiphytes on plants like straw [ 38 ]. Furthermore, bacteria used as competitors, like lactobacilli, cause a lowering of the pH, which also contributes to inhibiting the growth of other bacteria [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus sp. is one of many commensal epiphytes on plants like straw [ 38 ]. Furthermore, bacteria used as competitors, like lactobacilli, cause a lowering of the pH, which also contributes to inhibiting the growth of other bacteria [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It would not necessarily apply to other crops and fields where different species of AMF [s] dominate, or indeed where the species of PGPR [s] and the nature of the established symbiotic relationship potentially differ. The application of B. subtilis, an apparent antagonist in this study, may actually confer benefits if this is the main species of PGPR [s] for a given location and has established a symbiotic relationship with the AMF [s] [31,56]. The inoculation of agronomically important plant species therefore as PGPR [i] and AMF [i] would, based in this assertion, require the evaluation of the existing PGPR [s] and AMF [s] communities and the adaptation of the inoculated species accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…SMB MK386690 that was isolated from soil [ 79 ]. Currently, there are available data on species belonging to Sphingomonadaceae (e.g., Sphingomonas koreensis ) that are present in T. durum roots [ 166 ]. Xu et al [ 167 ] demonstrated that the inoculation of wheat seeds with a strain of Sphingomonas spp.…”
Section: Discussionmentioning
confidence: 99%